Communication and Job Satisfaction among Workers in the Department of Trade Union Affairs in the Northern State of Malaysia - Nasina Mat Desa; Muhammad Hasmi Abu Hassan Asaari; Azley Abd Razak; Nur Diyanah Abd Jabar (European Scientific Journal, ESJ, 2019)
This study aims to identify communication links with job satisfaction among workers in the Department of Trade Union Affairs. This study also examines the relationship between job satisfaction and communication with the effect of communication on job satisfaction. It has been noted that since recently, communication used in an organization has been extremely weak, resulting in job satisfaction. A total of 200 self-administered questionnaires were distributed among the workers in the Department of Trade Union Affairs. The study had received a total of 120 questionnaires with a 60% response rate. They were asked about their demographic information, communication, and job satisfaction. The tool for communication is based on the Satisfaction Communication Questionnaire, and the tool for job satisfaction is based on the Job Satisfaction Survey. The study concludes that communication has a significant relationship and impact on job satisfaction among workers in the department.